A dinâmica do fitoplâncton em uma várzea Amazônica variações sazonal e nictimeral (Várzea do Lago Grande de Curuai Pará, Brasil) - ALVES, Carla Patrícia Pereira (2011)
The river-floodplain systems are environments submitted a lateral overflow of river channel due the rains and/or underground waters. They are controlled by the type of climate, morphology and local effects. The lowland lakes are also highly productive because of the rich sources of primary carbon. The sediments transport and suspended and dissolved matter are done by the rivers between the land and aquatic phases. These phases strongly influence nutrient cycling, primary and secondary production and decomposition. The phytoplankton dynamics in tropical floodplain lakes is as variable as the seasonal and isolation patterns of flooding. For this reason, the aims of this work were i) to assess the rotation influence of potamophase and limnophase upon the phytoplankton of the Curuai Lake (PA, Brazil) and about the connectivity between other lakes, and ii) to evaluate the phytoplankton dynamics in a nictemeral cycling related to changes in CO2 in water, and what phytoplankton groups which were most important in this process. The phytoplankton community and environmental variables of the floodplain lakes of the Curuai Lake were sampled in the potamophase and limnophase (2009) and in a nictemeral cycling (2010). The informations summarized were obtained through the principal component analysis (PCA), canonical correspondence analysis (CCA), redundancy analysis (RDA) and nonmetric multidimensional scaling (MDS). The community structure was different among the periods with greater richness, density and phytoplanktonic biovolume in limnophase. There was predominance of Cryptophyceae (mainly Cryptomonas brasiliensis Castro, Bicudo & Bicudo) in potamophase and Cyanophyceae [Dolichospermum circinalis (formerly Anabaena circinalis) (Rabenh. ex Bornet et Flah.) Wacklin et al.] in limnophase, both influenced by environmental variables. In addition, the high phytoplanktonic biomass was favored by the highs temperatures and also responsible by the CO2 depletion in water caused by photosynthesis, which is reflected for the high carbon content in phytoplankton organisms. Despite the entry of water in the floodplain that connects the lakes, these environmental were distinct in relation a phytoplankton composition and a limnological variables. The phytoplanktonic community in Curuai Lake showed daily variation of biovolume because of high temperature and light availability. The development of persistent cyanobacteria bloom, with species predominance of Dolichospermum genius [functional group H1, D. spiroides (formerly A. spiroides) (Klebahn) Wacklin et al.] and Microcystis protocystis Crow (functional group M) caused the CO2 depletion in lake surface layer during the period of increased photosynthesis. The cyanobacteria bloom occurred mainly due to the attributes of group, which became it expressive competitors in relation another microalgae ones.